CORRECTION OF MICROELEMENT DEFICIENCIES IN CHILDREN WITH ATOPIC DERMATITIS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Atopic dermatitis (AD) is indeed a chronic inflammatory skin disease, and its development is associated with both genetic and immune factors. An integrated approach to the treatment of AD is key to achieving optimal results in therapy.